Significant improvement of physicians’ knowledge and clinical practice: an opportune, effective, and convenient continuing medical education program on functional dyspepsia - Chen, Jie; Bai, Tao; Liu, Jinsong; Xiong, Lishou; Wang, Weifeng; Wang, Huahong; Wang, Rongquan; Hou, Xiaohua (Frontiers in Medicine, 2024)
Aims This cohort study aimed to explore the effect of a one-day online continuing medical education (CME) on the improvement of physicians’ knowledge and clinical practice on functional dyspepsia (FD). Methods Physicians were invited to participate in this CME via medical education applications. FD training videos made in advance were sent to participants via a weblink. Before and after training, participants were required to finish the FD knowledge test and provide case information of FD patients. McNemar test, Wilcoxon rank-sum test, Freidman test, Chi-square test, quantile regression, and generalized estimating equations (GEE) were used to perform statistical analysis. Results There were 397 of 430 (92.33%) physicians finished this CME program. The total score of the FD knowledge test after training was significantly higher compared with before training [488.3 (468.3–510.0) vs. 391.7 (341.7–450.0), p < 0.001]. Particularly, physicians from primary hospitals show more increase in total scores than physicians from secondary and tertiary hospitals. According to the GEE model, receiving this online training was an independent predictor of physicians’ choice of upper gastrointestinal endoscopy in patients with FD [OR 1.73, 95%CI (1.09–2.73), p = 0.020], especially in PDS. Also, it was an independent predictor of physicians’ choice of acid-suppressive drugs in patients with FD [OR 1.30, 95%CI (1.03–1.63), p = 0.026], especially in EPS and PDS overlapping EPS. Conclusion This one-day online CME program effectively and conveniently improved physicians’ knowledge and clinical practice, providing new ideas for future CME and facilitating precise clinical management of FD patients with different subtypes especially in primary hospitals.